Orthodontic Treatment and Temporomandibular Joint Condylar Position Relationship with Disk Displacement (Magnetic Resonance Imaging Study) (Mustansiria Dental Journal, 2018)
Temporomandibular joint (TMJ) is a complex synovial articulation between themandibular condyle and the glenoid fossa of temporal bone. The question of whethera relationship exists between orthodontic treatment, abnormal condyle and diskposition, and temporomandibular disorders has been investigated for many years.Despite the abundance of studies, the question continues to trouble orthodontists.This study conducted to assess the relationship between orthodontic treatments,abnormal condyle and disk position, with temporomandibular disorders, and to studythe disk- condyle relationship in term of presence or absence of anterior diskdisplacement. By mean of Magnetic Resonance Imaging a cross sectionalinvestigation for the condyles of temporomandibular joints (TMJs) and disk positionwas conducted to 50 TMJs of 25 patients between 19-30 years of age who hadundergone orthodontic treatment (by upper and lower fixed orthodontic applianceswith extraction of maxillary first premolar only for treatment of class II division 1malocclusion), and 50 TMJs of 25 patients who had not yet received orthodontictreatment from the same class and matched age group.The results of this study showed that 30% of pre-treatment group have anteriordisk displacement in comparison to 26.0% of the post treatment group. The condyleposition is more concentric in post treatment group than pre-treatment, and theposition of the disk is not affected by orthodontic treatment. This conclude thatcondyle position of the TMJ may be affected by orthodontic treatment, but the diskposition is not.